2012
DOI: 10.1001/jama.2012.165
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Febrile Seizures and Epilepsy After Vaccination With Diphtheria, Tetanus, Acellular Pertussis, Inactivated Poliovirus, and Haemophilus Influenzae Type b

Abstract: DTaP-IPV-Hib vaccination was associated with an increased risk of febrile seizures on the day of the first 2 vaccinations given at 3 and 5 months, although the absolute risk was small. Vaccination with DTaP-IPV-Hib was not associated with an increased risk of epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 25 publications
0
51
2
1
Order By: Relevance
“…31 Other infant vaccines currently in use, for instance the DTaP, inactivated poliovirus, and Haemophilus influenza type B combined vaccine (DTaP-IPV-HIB), have not been associated with seizures in the United States, 32 although DTaP-IPV-HIB has been linked with increased febrile seizures in Denmark. 24 Other early childhood vaccines that have been associated with febrile seizures in the United States include inactivated influenza vaccine, but only in some influenza seasons, such as 2010-2011, and the 13-valent pneumococcal conjugate vaccine. 33 The risk for seizures after inactivated influenza vaccine and 13-valent pneumococcal conjugate vaccine was greatest if the vaccines were given the same day and in the second year of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Other infant vaccines currently in use, for instance the DTaP, inactivated poliovirus, and Haemophilus influenza type B combined vaccine (DTaP-IPV-HIB), have not been associated with seizures in the United States, 32 although DTaP-IPV-HIB has been linked with increased febrile seizures in Denmark. 24 Other early childhood vaccines that have been associated with febrile seizures in the United States include inactivated influenza vaccine, but only in some influenza seasons, such as 2010-2011, and the 13-valent pneumococcal conjugate vaccine. 33 The risk for seizures after inactivated influenza vaccine and 13-valent pneumococcal conjugate vaccine was greatest if the vaccines were given the same day and in the second year of life.…”
Section: Discussionmentioning
confidence: 99%
“…We did not include the first dose of hepatitis B vaccine (recommended shortly after birth) in the analysis. We examined only the first dose of each vaccine because others have observed that the first dose of certain vaccines (diphtheria, tetanus, and acellular pertussis vaccine [DTaP] 24 and measles-containing vaccines 16 ) may be the most reactogenic. We did not analyze specific "catch-up" vaccination schedules.…”
Section: Defining Exposure Status: Immunization On Time Versus Delayedmentioning
confidence: 99%
“…17 Likewise, Sun et al reported that the risk of febrile seizure may be increased after DTaP immunization, with relative risk of 6.02 on the first day and decreasing to 3.94 on the second day. 18 In conclusion, the DTwP-HB-Hib combined vaccine is immunogenic and safe, as well as comparable to the Hib vaccine given simultaneously with the DTwP-HB vaccine.…”
mentioning
confidence: 79%
“…1 However, development of neurologic deficits or epileptogenesis could not be related to vaccinations, in several independent epidemiologic studies. [2][3][4][5][6] In the general pediatric population, the risk of febrile seizures is twofold to fivefold increased on the day of administration of an inactivated vaccine and from day 5 up to 2 weeks after administration of a live attenuated vaccine. 2,5-9 A seizure within this risk period might be the first of an epilepsy syndrome, and parents might misinterpret the vaccination as the primary cause of the epilepsy.…”
Section: Discussionmentioning
confidence: 99%